Pengaruh Pajak Daerah, Retribusi Daerah dan PDRB Terhadap PAD Kota Medan - Ave Maria Togatorop; Putri Wahyuni; Albert Herlambang (Politeknik Ganesha Medan, 2026)
This study is motivated by the importance of Regional Original Revenue (PAD) as an indicator of regional financial independence influenced by local taxes, regional levies, and Gross Regional Domestic Product (GRDP). This study aims to analyze the effect of local taxes, regional levies, and GRDP on PAD in Medan City, both partially and simultaneously. This research uses a quantitative approach with secondary time series data covering 60 months from 2020 to 2024 using a saturated sampling technique. The analytical method employed is multiple linear regression using SPSS at a 5% significance level. The partial results show that local taxes have a t-value of 2.055 > 2.003 (t-table) with a significance of 0.045 < 0.05, regional levies have a t-value of 2.047 > 2.003 (t-table) with a significance of 0.045 < 0.05, and GRDP has a t-value of 2.005 > 2.003 (t-table) with a significance of 0.050 ≤ 0.05 (at the significance threshold), indicating that all variables have a positive and significant effect on PAD. Simultaneously, the F-value is 8.662 > 2.769 (F-table) with a significance of 0.000 < 0.05, indicating that all independent variables jointly have a significant effect on PAD. The coefficient of determination (R²) is 0.317 or 31.7%, indicating that the variables in this study explain variations in PAD, while the remaining 68.3% is influenced by other variables outside the study. The implication of this study is the importance of optimizing local taxes, regional levies, and regional economic activities to increase PAD. Future research is recommended to include additional variables and extend the observation period.